2008
DOI: 10.1037/a0013323
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting exposure and experiential therapies for complex posttraumatic stress disorder.

Abstract: In this paper, the authors compare and contrast two psychotherapy paradigms for the treatment of complex posttraumatic stress disorder (PTSD): a behavioral therapy (prolonged exposure; PE) and an experiential therapy (Accelerated Experiential Dynamic Psychotherapy; AEDP). PE has received strong research support as an effective treatment for PTSD. The scientific evidence for experiential therapy is sparser, but also positive. In addition, clinical and research evidence suggest that (a) experiential processes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 96 publications
1
77
0
Order By: Relevance
“…The political nature of torture as part of inter-group violence, contrasted by interpersonal violence should help develop targeted interventions more appropriate to this core trauma type. The potential effects of torture on decreased re-experiencing may help explain why clinicians report that traditional exposure therapy may be contraindicated with torture survivors and victims of severe trauma in general (e.g., Gleiser, Ford, & Fosha, 2008;Kira, 2010). Intervention based on PTSD model and re-experiencing (e.g., traditional exposure therapy) may not be effective for some of them as their symptoms may be more severe.…”
Section: Discussionmentioning
confidence: 99%
“…The political nature of torture as part of inter-group violence, contrasted by interpersonal violence should help develop targeted interventions more appropriate to this core trauma type. The potential effects of torture on decreased re-experiencing may help explain why clinicians report that traditional exposure therapy may be contraindicated with torture survivors and victims of severe trauma in general (e.g., Gleiser, Ford, & Fosha, 2008;Kira, 2010). Intervention based on PTSD model and re-experiencing (e.g., traditional exposure therapy) may not be effective for some of them as their symptoms may be more severe.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been suggested that EMDR is just another form of exposure (Lohr, Tolin, & Lilienfeld, 1998), although this has been rebutted (e.g., Perkins & Rouanzoin, 2002). Gleiser, Ford, and Fosha (2008) concluded that prolonged exposure therapies are inherently different from experiential therapies. About this, Greenberg (2007b) states:…”
Section: Is Tes the Same As Exposure?mentioning
confidence: 99%
“…The patient is provided the opportunity to express his or her experience while in the presence of a safe other, reducing the feelings of shame and isolation that often plague trauma survivors: "telling one's story promotes a sense of knowing and being known" (McLeod, 2004). It should be noted that while both CPT and the AEDP-Writing model focus on both cognitive and affective processing, the CPT model places greater emphasis on cognition, and the AEDP-Writing model on affect, because of the focus in AEDP on affect (Gleiser, Ford & Fosha, 2008).…”
Section: Expressive Writing and Traumamentioning
confidence: 99%
“…As Fosha (2006a) writes, "There is a world of difference between being alone with overwhelming emotions and being with a trusted other in the affect storm" (p. 570). A related idea is expressed in the words of Gleiser, Ford, and Fosha (2008). They write that AEDP aims to help PTSD patients find relief via transforming diffuse distress, fear, and anxiety into more fully articulated and better regulated emotions, memories, and adaptive action on behalf of the self.…”
Section: Aedp and Traumamentioning
confidence: 99%
See 1 more Smart Citation